The Frequencies of Gastroesophageal and Extragastroesophageal Symptoms in Patients with Mild Erosive Esophagitis, Severe Erosive Esophagitis, and Barrett's Esophagus in Taiwan. (12th August 2013) - Kao, Sung-Shuo; Chen, Wen-Chih; Hsu, Ping-I; Chuah, Seng-Kee; Lu, Ching-Liang; Lai, Kwok-Hung; Tsai, Feng-Woei; Chang, Chun-Chao; Tai, Wei-Chen
Abstract : Background . Gastroesophageal reflux disease (GERD) may present with gastroesophageal and extraesophageal symptoms. Currently, the frequencies of gastroesophageal and extragastroesophageal symptoms in Asian patients with different categories of GERD remain unclear. Aim . To investigate the frequencies of gastroesophageal and extragastroesophageal symptoms in patients with mild erosive esophagitis, severe erosive esophagitis, and Barrett's esophagus of GERD. Methods . The symptoms of symptomatic subjects with (1) Los Angeles grade A/B erosive esophagitis, (2) Los Angeles grade C/D erosive esophagitis, and (3) Barrett's esophagus proven by endoscopy were prospectively assessed by a standard questionnaire for gastroesophageal and extragastroesophageal symptoms. The frequencies of the symptoms were compared by Chi-square test. Result . Six hundred and twenty-five patients (LA grade A/B: 534 patients; LA grade C/D: 37 patients; Barrett's esophagus: 54 patients) were assessed for gastroesophageal and extragastroesophageal symptoms. Patients with Los Angeles grade A/B erosive esophagitis had higher frequencies of symptoms including epigastric pain, epigastric fullness, dysphagia, and throat cleaning than patients with Los Angeles grade C/D erosive esophagitis. Patients with Los Angeles grade A/B erosive esophagitis also had higher frequencies of symptoms including acid regurgitation, epigastric acidity, regurgitation of food, nausea, vomiting, epigastric fullness, dysphagia, foreign body sensation of throat, throat cleaning, and cough than patients with Barrett's esophagus. Conclusion . The frequencies of some esophageal and extraesophageal symptoms in patients with Los Angeles grade A/B erosive esophagitis were higher than those in patients with Los Angeles grade C/D erosive esophagitis and Barrett's esophagus. The causes of different symptom profiles in different categories of GERD patients merit further investigations.